Simulation and optimization of control rod sequence exchange operations for a pressurized water reactor under Mechanical Shim control strategy. (July 2019) - He, Zhengxi; Sun, Jian; Wang, Shu; Wang, Pengfei; Song, Hongbing
Highlights: CRSE operations under MSHIM control are simulated for the whole cycle life of the AP1000 reactor. Dynamic characteristics of the reactor during CRSE transients are analyzed with feasibility of the CRSE logic demonstrated. Trigger rod position in the CRSE logic is optimized with the performance and effectiveness of the optimization assessed. Abstract: The purpose of this paper is to study dynamic characteristics of the AP1000 reactor during control rod sequence exchange (CRSE) operations under the Mechanical Shim (MSHIM) control strategy so as to assess the feasibility of and further optimize the CRSE logic. For this purpose, a dynamic simulation platform was developed in MATLAB/Simulink environment first, with implementation of a one-dimensional nodal core model and the reactor power control system integrating the basic MSHIM control logic and the CRSE logic. Based on the platform, simulation studies of typical CRSE transients of the AP1000 reactor at the beginning of cycle life (BOC), middle of cycle life (MOC) and end of cycle life (EOL) have been performed to determine the performance of the current CRSE design. From the simulation results, impacts of the CRSE operations on the reactor power and axial power difference have been analyzed. It shows that the AP1000 reactor can accomplish the CRSE operations smoothly and safely implementing the CRSE logic. To further improve the control performance of the reactor during CRSE operations, the trigger rod position, a key factor in the CRSE design, has been optimized with the optimization results assessed through dynamic simulations against the above CRSE transients. The simulation results have demonstrated the effectiveness of the optimization.